2012
DOI: 10.1177/0021998312437000
|View full text |Cite
|
Sign up to set email alerts
|

Bulk composites from microfibrillated cellulose-reinforced thermoset starch made from enzymatically degraded allyl glycidyl ether-modified starch

Abstract: Microfibrillated cellulose consists of nanoscale bundles of elementary microfibrils prepared, e.g. by the defibrillation of delignified wood pulp fibres in high-pressure homogenizers. In this study, microfibrillated cellulose was used to reinforce a thermoset starch plastic. The starch was modified with allyl glycidyl ether with a degree of substitution of 1.3, which was further hydrolyzed with α-amylase for 18 h yielding significantly improved processing properties. Dry premixes of all constituents were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The plot shows that for small transverse Young's moduli and shear moduli of the CNF, the models give similar results. 37 Published works on CNF lms typically investigate the tensile behaviour of the lm rather than addressing the mechanical properties of the nanobrils themselves. For a high transverse and shear modulus, both the Cox model and the Krenchel model predict a stiffness that is less the half of the stiffness predicted by CLT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plot shows that for small transverse Young's moduli and shear moduli of the CNF, the models give similar results. 37 Published works on CNF lms typically investigate the tensile behaviour of the lm rather than addressing the mechanical properties of the nanobrils themselves. For a high transverse and shear modulus, both the Cox model and the Krenchel model predict a stiffness that is less the half of the stiffness predicted by CLT.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies focus on the preparation of CNF lms, which is usually technically more straightforward than to produce CNF-based foams 36 and bulk composites. 37 Published works on CNF lms typically investigate the tensile behaviour of the lm rather than addressing the mechanical properties of the nanobrils themselves. By applying CLT, an estimation of the elastic properties of the CNFs can however be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Varieties of cross-linkers are reported to be used for enhancement of properties of the composites. Duanmu et al has used ethylene glycol dimethacrylate to cross-link allylglycidal ether-modified starch with softwood fibers. Among the water-soluble cross-linkers, the use of DMDHEU, GA, and NMA have been cited in the literature for improvement of various properties of wood polymer composites. Compared to the untreated composites, water uptake and dimensional swelling of the GA- and DMDHEU-treated wood composites were decreased, whereas flexural and tensile properties were improved . Improvements in water resistance, thermal resistance, and mechanical properties of wood starch composites are required in order to use it in outdoor applications.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literatures pertaining to wood polymer composites have reported the use of at least one water-insoluble component in the composites. There are a few reports of using modified starch and water-soluble initiators for the preparation of wood starch composites. To the best of our knowledge, there is neither any detailed investigation nor any comparison among different cross-linkers used for improving the properties of wood starch composites.…”
Section: Introductionmentioning
confidence: 99%
“…12−14 However, in several studies, cellulose and water have been found to interfere with the polymerization reactions and to introduce defects in the composites. 15,16 Waterborne polymers are mainly used as adhesives and coatings. In another approach, cellulose suspensions are filtered to yield thin films, which can be embedded in and cured with thermosetting resins 17 or be sandwiched between polymer sheets and hotpressed into laminates.…”
Section: ■ Introductionmentioning
confidence: 99%